2018
DOI: 10.1007/s00429-018-1622-4
|View full text |Cite
|
Sign up to set email alerts
|

Complementary expression of calcium binding proteins delineates the functional organization of the locomotor network

Abstract: Neuronal networks in the spinal cord generate and execute all locomotor-related movements by transforming descending signals from supraspinal areas into appropriate rhythmic activity patterns. In these spinal networks, neurons that arise from the same progenitor domain share similar distribution patterns, neurotransmitter phenotypes, morphological and electrophysiological features. However, subgroups of them participate in different functionally distinct microcircuits to produce locomotion at different speeds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 134 publications
(216 reference statements)
1
18
2
Order By: Relevance
“… 52 A recent study of the expression of calcium-binding proteins in motoneurons in the spinal cord of the locomotor system in zebrafish revealed that CR was highly expressed in fast motoneurons, but not in slow motoneurons. 53 This is in contrast to our findings in the oculomotor system, where CR is present only in a subpopulation of neurons activating multiply innervated tonic muscle fibers with slow contractions, 54 whereas the motoneurons activating singly innervated twitch muscle fibers lack CR, but contain parvalbumin. 55 , 56 On the other hand, in the rostral mesencephalon a subgroup of saccadic premotor burst neurons (only those involved in upgaze) contain CR.…”
Section: Discussioncontrasting
confidence: 99%
“… 52 A recent study of the expression of calcium-binding proteins in motoneurons in the spinal cord of the locomotor system in zebrafish revealed that CR was highly expressed in fast motoneurons, but not in slow motoneurons. 53 This is in contrast to our findings in the oculomotor system, where CR is present only in a subpopulation of neurons activating multiply innervated tonic muscle fibers with slow contractions, 54 whereas the motoneurons activating singly innervated twitch muscle fibers lack CR, but contain parvalbumin. 55 , 56 On the other hand, in the rostral mesencephalon a subgroup of saccadic premotor burst neurons (only those involved in upgaze) contain CR.…”
Section: Discussioncontrasting
confidence: 99%
“…The specificity of the primary antisera used in the present study has been confirmed by the manufacturers and by numerous researchers in various previous papers (Zimmermann and Schwaller, ; Drexel et al ., ; Mészár et al ., ; Berg et al ., ) including our team (Najdzion et al ., ; Zakowski et al ., ; Hermanowicz‐Sobieraj et al ., ; Równiak et al ., ). The rabbit anti‐CB (CB‐38), mouse anti‐CB (300), and mouse anti‐CR (6B3) antisera include immunoblots of the guinea pig brain homogenates, which were specifically stained by these antibodies, exhibiting bands at 28, 28, and 29 kDa, respectively (manufacturer's technical information).…”
Section: Methodsmentioning
confidence: 99%
“…Retrograde labeling of axial motor neurons was performed in anesthetized zebrafish with 0.03% tricaine methane sulfonate (MS-222, E10521; Sigma-Aldrich) by using dye injections with tetramethylrhodamine-dextran (3,000 molecular weight, D3307; Thermo Fisher) or with biotinylated dextran (3,000 molecular weight, D7135; Thermo Fisher) into all muscles or into specific muscle fiber types (slow, intermediate, or fast) in myotomes 14–16 ( 21 , 42 , 43 ). All of the injected animals were allowed to recover for 5 h to overnight to help the retrograde transport of the tracer.…”
Section: Methodsmentioning
confidence: 99%